Enhanching Assessment as Learning: The Influence of Language Assessment Literacy on Indonesian EFL Students’ Writing - Entika Fani Prastikawati; Samantha Curle; Pryla Rochmahwati; Maria Yosephin Widharti Lestari; Lusia Maryani Silitonga; Raveenthiran Vivekanantharasa (JOLLT Journal of Languages and Language Teaching, 2026)
This study examines the impact of enhancing Language Assessment Literacy (LAL) on Indonesian EFL students’ writing development through Assessment as Learning (AaL) practices. Unlike most research that emphasizes teacher-focused LAL, this study shifts attention to learners, exploring how assessment knowledge, particularly through rubrics, can promote metacognitive awareness, autonomy, and improved writing outcomes. A mixed-methods design was employed with 84 senior high school students randomly assigned to experimental and control groups. Results showed no significant differences between groups prior to the intervention. However, post-test scores indicated a significant advantage for the experimental group (M = 16.69) compared to the control group (M = 8.91), with a large effect size (η² = .82), confirming the effectiveness of LAL-based pedagogy. Qualitative interview data revealed that students’ attitudes toward LAL strongly shaped its classroom integration. Although learners initially reported limited experience, low confidence, and concerns about the reliability of peer assessment, they ultimately expressed positive perceptions of LAL, highlighting its role in clarifying writing expectations, supporting reflection, and fostering learner autonomy. These findings suggest that embedding LAL in EFL writing instruction can transform assessment into a learner-centered process that enhances both writing performance and self-regulated learning. Pedagogically, the study underscores the importance of scaffolding and supportive implementation of student-centered assessment practices. However, the study is limited by its short intervention period and context-specific sample.